Posterior cingulate epilepsy: clinical and neurophysiological analysis. Issue 1 (7th August 2013) - Enatsu, Rei; Bulacio, Juan; Nair, Dileep R; Bingaman, William; Najm, Imad; Gonzalez-Martinez, Jorge
Abstract : Objective: Posterior cingulate epilepsy (PCE) is misleading because the seizure onset is located in an anatomically deep and semiologically silent area. This type of epilepsy is rare and has not been well described yet. Knowledge of the characteristics of PCE is important for the interpretation of presurgical evaluation and better surgical strategy. The purpose of this study was to better characterise the clinical and neurophysiological features of PCE. Methods: This retrospective analysis included seven intractable PCE patients. Six patients had postcingulate ictal onset identified by stereotactic EEG (SEEG) evaluations. One patient had a postcingulate tumour. We analysed clinical semiology, the scalp EEG/SEEG findings and cortico-cortical evoked potential (CCEP). Results: The classifications of scalp EEG were various, including non-localisible, lateralised to the seizure onset side, regional parieto-occipital, regional frontocentral and regional temporal. Three of seven patients showed motor manifestations, including bilateral asymmetric tonic seizures and hypermotor seizures. In these patients, ictal activities spread to frontal (lateral premotor area, orbitofrontal cortex, supplementary motor area, anteior cingulate gyrus) and parietal (precuneus, posterior cingulate gyrus, inferior parietal lobule (IPL), postcentral gyrus) areas. Four patients showed dialeptic seizures or automotor seizures, with seizure spread to medial temporal or IPL areas. CCEP was performed in four patients, suggesting electrophysiological connections from the posterior cingulate gyrus to parietal, temporal, mesial occipital and mesial frontal areas. Conclusions: This study revealed that the network from the posterior cingulate gyrus and the semiology of PCE (motor manifestation vs dialeptic/automotor seizure) varies depending upon the seizure spread patterns.